The ancient magus' bride. Volume 19 - Yamazaki, Kore; MacFarlane, Ysabet Reinhardt (Ancient magus' bride, 2023)
Philomela finally stops clasping her hands in passive prayer, and instead reaches them out for help. Meanwhile, Lizbeth gives in to blind obsession, merging with the forbidden Testament. Then a third, unexpected party joins the fray--a curse designed to kill a mother. All actors are in place on a chaotic stage, and when the goddess Morrígan finally makes her entrance, the story of one fraught family comes to an end.